Frustration and aggression of military drivers on the road. - de Guzman, Peter Jempsun
This study identified levels of frustration and aggression of military drivers with respect to the age and sex of offending motorist through using purposively designed simulated scenarios and interview. Two hundred eigteen (n=218) military drivers from the Philippines Navy, stationed in Metro Manila and Cavite, participated in the study. Interviews were also conducted with key informants to understand and provide solutions in instances of driver frustration and aggression. Upon examination of mean scores, results showed young motorist frustrated military drivers more. In addition, the sex of the motorist frustrated military drivers, specially when motorists were male. Further, an interaction effect was also discovered with the mean score of frustration being highest when other motorist were young males.